Recent advancements in nanocellulose reinforced biopolymer hybrid composites: A review - Habib, Abdul; Firdaus, A. H.M.; Sapuan, S. M.; Abral, Hairul; Azka, Muhammad Adlan; Zainudin, E. S.; Atiqah, A.; Yusuf, J. (Elsevier, 2025)
Numerous innovative developments have been made in the use of composite materials for a range of applications. The field of reinforcement in composite materials is currently experiencing significant advancements, marked by an abundance of novel findings such as the incorporation of nanocellulose, biomaterials, and hybrid reinforcement composites. However, the hybridization of composites often leads to agglomeration and weak interfacial bonding because nanoparticles have higher surface areas. Nanocellulose functions as a bio-dispersant in the hybrid composites. The studies reviewed here demonstrate that nanocellulose biopolymer hybrid composites possess enhancement in physical properties, increase the tensile strength, improve the thermal stability, morphological properties, enhanced antibacterial activity, the conductivity, and optical properties, compared to native polymers. The enhanced interactions between the biopolymer matrix and the nanomaterials and their hybrid reinforcements are responsible for the improvements. Nanocellulose biopolymer hybrid composites have outstanding properties and exhibit biodegradability empowering them an ideal material for many applications including food packaging, tissue engineering, electrical components, and water collection. This review investigates emerging applications like sensors, packaging, biomedical, and papers, in the field of green composite materials. Besides, various challenges related with economic and environment aspects for are also discussed.